The Relationship Between Patients' Knowledge and Attitude Regarding Gastritis Prevention in the Class 1 Treatment Room of Doloksanggul Regional Hospital - Mery Lestari Simanjuntak; Hengky Simamora (Jurnal EduHealth, 2025)
One of the factors influencing human resources is health, which plays a significant role. The purpose of this study was to determine the relationship between patient knowledge and attitudes regarding gastritis prevention.This study used a quantitative cross-sectional design. The population was 58 people and the sample size was 58, using a total sampling method. A 95% confidence level (α = 0.05) was used. The results of this study indicate a correlation between knowledge and attitudes. Using the chi-square test with a 95% confidence level (α = 0.05) and df = 4, the arithmetic mean square (A) was 15.204, > chi-square (Table 9.488). This indicates a correlation between knowledge and gastritis prevention. Using the Chi-square test with a 95% confidence level (α=0.05) and df=2, the calculated square was 10.979 > chi-square table 5.591, indicating a relationship between attitudes and gastritis prevention.